Chinese trade price and Yuan's valuation. (10th February 2019) - Gao, Yichen; Gan, Li; Li, Qi
Abstract: This paper studies how the major economic events would have affected Chinese yuan's nominal exchange rate against US dollar from 1989 to 2013. The traditional average treatment effect estimation methods cannot be used to consistently estimate yuan's pegged exchange rate. We develop a new estimation strategy by combining a novel panel data method (proposed by Hisao, Ching and Wan) and the purchasing power parity theory. Based on this new estimation strategy, we find that during the period of pegging to US dollar, Chinese yuan were undervalued. Before the 1997 Asian Financial Crisis, the pegged exchange rate regime starting from January 1994 made the yuan undervalued by 2.62%. China's accession to WTO caused yuan undervalued by 36.60%. After the reform of Chinese exchange rate policy in July 2005, the undervaluation of the yuan was reduced to only 0.76%. Yuan was undervalued again by 20.43% because of 2008 China's economy stimulus package. The policy reform in June 2010 made yuan overvalued by 14.40%. We conclude that Chinese fixed exchange rate policy indeed undervalued the yuan, especially after its accession to WTO. The recent reforms of Chinese exchange rate policy made progresses in re‐evaluating the yuan.